Proses Produksi Soft Magnetic Composite (SMC) Berbahan Dasar Fe - Waloyo, Hery Tri; Firmansyah, Muhammad Gilang; Setiyawan, Khanif; Mujianto, Agus (Jurnal Teknik Mesin Indonesia, 2025)
This study discuss in various production methods of iron-based Soft Magnetic Composite (SMC) and to identify the most effective production. The increase in carbon emissions and the need for alternative energy drive the development of electromagnetic technology, including the use of SMC in electric motors. The method used in this study is a literature review, by reviewing relevant articles from national and international journals. The results of the study indicate that traditional production methods and Additive Manufacturing (AM) are the two main methods used in SMC production. Among these methods, the traditional production method with Powder Metallurgy (PM) technology proved to be more effective in producing SMC with better quality and more efficient production processes. This research provides in-depth insights into various SMC production techniques and can serve as a foundation for future research in the development of electromagnetic materials.